Acquired hemophilia A after vaccination against SARS-CoV-2 with the mRNA-1273 (Moderna) vaccine. Issue 5 (15th September 2022) - Melmed, Ava; Kovoor, Andrew; Flippo, Korie
Abstract: Acquired hemophilia A is a rare bleeding diathesis most typically seen in systemic rheumatic disease, solid and hematologic malignancies, and pregnancy. We present a case of this condition that occurred immediately after vaccination against SARS-CoV-2 with the mRNA-1273 (Moderna) vaccine.